1995
DOI: 10.1128/jb.177.22.6462-6468.1995
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Bacillus subtilis groE regulatory mutants: evidence for orf39 in the dnaK operon as a repressor gene in regulating the expression of both groE and dnaK

Abstract: An inverted repeat sequence known as CIRCE (controlling inverted repeat of chaperone expression) in the Bacillus subtilis groE operon has been suggested to function as an operator. To identify the regulatory gene directly or indirectly involved in CIRCE-mediated heat-inducible groE expression, B. subtilis WBG2, carrying an integrated groE-bgaB transcription fusion in the amyE locus, was mutagenized. Dark blue colonies formed at 37؇C represent mutants which constitutively produce BgaB (a thermostable ␤-galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
1
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 39 publications
(43 reference statements)
4
119
1
3
Order By: Relevance
“…The correlation between the markedly lower oA activity and the temperature sensitivity of B. subtilis DB1005 at 49 "C suggests that the level of activity of oA is the limiting factor for DB1005 growth at high temperature. Furthermore, the lack of induction of groE message in vitro in the presence of wild-type oA above 37 "C was probably due to the absence of repressors (Yuan & Wong, 1995) in the system, which thus allowed the groE promoter to express constitutively.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between the markedly lower oA activity and the temperature sensitivity of B. subtilis DB1005 at 49 "C suggests that the level of activity of oA is the limiting factor for DB1005 growth at high temperature. Furthermore, the lack of induction of groE message in vitro in the presence of wild-type oA above 37 "C was probably due to the absence of repressors (Yuan & Wong, 1995) in the system, which thus allowed the groE promoter to express constitutively.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription of class I genes, which code for classical chaperones, is A dependent and regulated by the HrcA repressor (14,29,31). The class II genes respond not only to heat but also to other stresses such as exposure to ethanol or salt, starvation for glucose or phosphate, or growth under anaerobic conditions.…”
mentioning
confidence: 99%
“…Two working groups reported that the HrcA (ORF39) of B. subtilis regulated the expression of the groE and dnaK genes by associating with the CIRCE element (24)(25)(26). We further analyzed the role of hrc37 in heat-shock response by isolating the hrc37 disrupt mutant.…”
Section: Discussionmentioning
confidence: 99%